1987
DOI: 10.1111/j.1469-8137.1987.tb02930.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF EXPERIMENTAL DEFOLIATION ON A POPULATION OF PEDUNCULATE OAK (QUERCUS ROBUR L.)

Abstract: SUMMARYAn experiment simulating defoliation at three levels of severity was conducted on 196 young oaks in a plot at Wolverhampton.In comparison with control plants, defoliation caused (1) earlier production of growth spurts (which are normal in undefoliated trees) and formation of more lateral branches, which were susceptible to winter frost damage; (2) production of more abundant, smaller leaves; (3) reduced diameters of main stems, from which can be calculated growth rates, varying with both defoliation tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 4 publications
4
20
0
1
Order By: Relevance
“…It has been shown that oak can survive repeated browsing by herbivores (Shaw, 1974;Hilton et al, 1987). Langbein (1997) found that oak saplings at or below the height of the surrounding field vegetation were often several years old, but remained at heights less than 35 cm and often less than 20 cm due to persistent browsing over the years.…”
Section: Effects Of Browsing On Oak Seedlings and Implications Of Excmentioning
confidence: 97%
“…It has been shown that oak can survive repeated browsing by herbivores (Shaw, 1974;Hilton et al, 1987). Langbein (1997) found that oak saplings at or below the height of the surrounding field vegetation were often several years old, but remained at heights less than 35 cm and often less than 20 cm due to persistent browsing over the years.…”
Section: Effects Of Browsing On Oak Seedlings and Implications Of Excmentioning
confidence: 97%
“…Conformément àde nombreux résultats obtenus en conditions contrôlées (Barnola et al ., 1990;Hilton et al .,1987;Ericsson etal .,1980),les feuilles,parvenant àleur taille finale, détournent àleur profit les nutriments quip ermettraient le développement des bourgeons. Cecie xpliquel e repos forcéd u bourgeon terminalaprès complèteé longation de l'UC1e t sa reprised 'allongement précoce sil es feuilles sont retirées.Cecie xpliqueé galement le démar-rage de ramifications sur l'UC1.…”
Section: Sur Les Corrélations Physiologiques Entrel Es Feuilles Et L'unclassified
“…Initially bluebell bulbs, (Hyacinthoides non-scripta) and clonal plants of Lamiastrum ga/eobdo/on, (yellow archangel), and Oxalis acetosel/a, (wood sorrel), were planted in a 9 year old experimental oak plantation (HILTON, PACKHAM, and WILLIS, 1987) to which four litter treatments had been applied in a Latin square design (Fig. 1).…”
Section: Litter Experimentsmentioning
confidence: 99%